2009
DOI: 10.2134/agronj2008.0154x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Response to Chicken Litter in Rotation with Corn in Clayey Soil

Abstract: Poultry litter may benefi t continuous cotton (Gossypium hirsutum L.) production in the heavier Midsouth soils in the same way as crop rotation. Th e objective of this research was to determine the eff ectiveness of poultry litter in maintaining yield of continuous cotton compared with cotton-corn (Zea mays L.) rotation in the Black Belt Prairie clay soils of Mississippi. Th e research was conducted in a Catalpa silty clay loam soil in northern Mississippi. Th ree main plots with the sequence cotton-cotton-cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
6
22
0
Order By: Relevance
“…Approximately, 85% of plant K concentration data collected from forages (including bermudagrass, fescue, turfgrass, and forage-mix), both composted and fresh PL treatments produced higher forage K than the inorganic NPK treatments (Warman and Cooper, 2000;Warren et al, 2008;Wood et al, 1993) and showed a positively linear response in tissue K concentration with litter application (Warman and Cooper, 2000). Our results were consistent with the previous studies of cotton (Tewolde et al, 2011;Tewolde et al, 2009b), where fertilizing with litter slightly increased bulk leaf K concentration and had approximately the same stem or reproductive K concentration as cotton fertilized with IF. The slightly higher K concentration in plants indicated that K concentration in PL can satisfy plant growth requirements, which mainly due to K in manure being mostly in inorganic forms, therefore virtually all the K is available for plant uptake.…”
Section: Nutrient Concentrationsupporting
confidence: 90%
“…Approximately, 85% of plant K concentration data collected from forages (including bermudagrass, fescue, turfgrass, and forage-mix), both composted and fresh PL treatments produced higher forage K than the inorganic NPK treatments (Warman and Cooper, 2000;Warren et al, 2008;Wood et al, 1993) and showed a positively linear response in tissue K concentration with litter application (Warman and Cooper, 2000). Our results were consistent with the previous studies of cotton (Tewolde et al, 2011;Tewolde et al, 2009b), where fertilizing with litter slightly increased bulk leaf K concentration and had approximately the same stem or reproductive K concentration as cotton fertilized with IF. The slightly higher K concentration in plants indicated that K concentration in PL can satisfy plant growth requirements, which mainly due to K in manure being mostly in inorganic forms, therefore virtually all the K is available for plant uptake.…”
Section: Nutrient Concentrationsupporting
confidence: 90%
“…Jn-Baptiste et al (2012) found no difference in yield among CF application and two PL rates in Kentucky. Tewolde et al (2009a) reported 9.2% less grain yield in corn from PL compared with that from CF in Mississippi and argued that the 50% N availability from PL may be erroneous because the PL applied met the target rate of the CF. In this study, similar grain yield from the low PL, which supplied significantly lower N compared with the NH 4 NO 3 (67.5 vs 145 kg ha j1 ), and the significantly lesser grain yield (13%) from the NH 4 NO 3 compared with that of the medium PL rate (5,045 vs 4,450 kg ha j1 ), which supplied similar N, seem to support the argument by Tewolde et al (2009) that the 50% available N assumption from the PL might be erroneous.…”
Section: Corn Grain Yieldmentioning
confidence: 99%
“…For example, Tewolde et al (2009b) found that cotton fertilized with 13.5 Mg ha À1 litter in a clayey soil in northern Mississippi had less green foliage and much less bulk leaf N concentration but produced as much as 26 % more lint yield than cotton that received the locally recommended inorganic fertilization. For example, Tewolde et al (2009b) found that cotton fertilized with 13.5 Mg ha À1 litter in a clayey soil in northern Mississippi had less green foliage and much less bulk leaf N concentration but produced as much as 26 % more lint yield than cotton that received the locally recommended inorganic fertilization.…”
Section: Cotton Appearance Not Indicator Of Performance Of Poultry LImentioning
confidence: 99%
“…Damage to cotton yield by parasitic nematodes is a major concern to the extent that nematicides are often a key component of best management practices in the southern and southeastern US. Applying litter to soil has been shown to stimulate soil microorganisms (Riegel and Noe 2000;Pratt and Tewolde 2009;Tewolde et al 2009b) and it has also been shown to reduce harmful nematodes (Riegel and Noe 2000). The effectiveness of litter in suppressing harmful nematodes may be associated with its stimulating effect on beneficial soil microorganisms (Riegel and Noe 2000).…”
Section: Poultry Litter May Suppress Harmful Plant Parasitic Nematodesmentioning
confidence: 99%